Self-concept 6 months after traumatic brain injury and its relationship with emotional functioning - Mascialino, Guido; Cañadas, Viviana; Valdiviezo-Oña, Jorge; Rodríguez-Lorenzana, Alberto; Arango-Lasprilla, Juan Carlos; Paz, Clara (Frontiers in Psychology, 2022)
This is an observational exploratory study assessing self-concept and its association with depression, anxiety, satisfaction with life, and quality of life six months after experiencing a traumatic brain injury. Participants were 33 patients who suffered a traumatic brain injury six months before the assessment. The measures used in this study were the Repertory Grid Technique, Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Satisfaction With Life Scale, and the Quality of Life after Brain Injury. We calculated Euclidean distances to assess differences in pre-and post-injury self-perception, as well as the proportion of opposed pole construct rating and polarization to understand how they are associated with the scores of the other offered measures. We found that the distance between the present and ideal self, as well as the distance between the present self and the self before the lesion showed moderate positive correlations with depression, and negative correlations with satisfaction with life and quality of life. Also, for the present and self before the lesion, the proportion of opposed pole ratings was correlated with depression symptoms, quality, and satisfaction with life, while for the present self and the ideal self this proportion was correlated with all the measures. The proportion of polarization of the present self and the total polarization was negatively correlated with symptom measures. The repertory grid might facilitate a greater understanding of self-concept after traumatic brain injury. This information could be used to guide treatments that address the emotions related to distances observed in the perception of the self.